Development of PRO-140 (Leronlimab) as a treatment for COVID-19 - Lalezari, Jacob (Henry Stewart Talks, 2020)
Previous indications for Leronlimab, Leronlimab is a CCR5 receptor antagonist, CCR5 receptor function in inflammation and disease, Clinical limitations of blocking CCR5 receptors, How will Leronlimab be used in the clinic?, When can we expect a preliminary approval?, **We are informed that key findings were submitted for publication on 24 April 2020 **